AB0682 CIRCULATING FIBROCYTES IN LIMITED CUTANEOUS SYSTEMIC SCLEROSIS PATIENTS: CORRELATION WITH DERMAL THICKNESS. (June 2019) - Ruaro, Barbara; Soldano, Stefano; Smith, Vanessa; Paolino, Sabrina; Pizzorni, Carmen; Contini, Paola; Montagna, Paola; Tardito, Samuele; Cutolo, Maurizio
Abstract : Background: Systemic sclerosis (SSc) is characterized by early skin impairment (1, 2) and the modified Rodnan skin score (mRSS) is the validated method to assess the severity of this impairment. Whilst skin high frequency ultrasound (US) is a relatively new technique to measure dermal thickness (DT) (2-4). Recent findings have reported the important contribution circulating fibrocytes make in the early stage of dermal repair and fibrosis. Indeed, as fibrocytes may be an important source of activated fibroblasts/myofibroblasts, it is reasonable to presume that they could be responsible for the increase in these cells observed in the tissue of SSc patients (5-7). Objectives: The aim of this study was to identify any correlation between the modified Rodnan skin score (mRSS), dermal thickness (DT), measured by skin high frequency ultrasound (US) and the percentage of circulating fibrocytes in patients with limited cutaneous systemic sclerosis (lcSSc). Methods: After obtaining approval and written informed consent and the Ethics Committee approval 8 lcSSc patients (7 females, 1 male) and 5 (4 females, 1 male) age-matched healthy volunteers (CNT) were enrolled. The lcSSc patients fulfilled the 2013 aCR/EULAR criteria for SSc (8). DT was evaluated by both mRSS and US (18 and 22 MHz probes), in all SSc patients and CNT, in the standard 17 skin areas evaluated by mRSS. The percentage of circulating fibrocytes was obtained by isolating them from the peripheral blood mononuclear cells (PBMCs) in all lcSSc patients and CNTs. Non-parametric tests were used for the statistical analysis. Results: The percentage of circulating fibrocytes was positively correlated with DT-US, evaluated by the 22 MHz and the 18 MHz probes (p=0.04 and p=0.03, respectively) and mRSS (p=0.04) in lcSSc patients. Conversely, there was no correlation between these parameters in the CNT group (p>0.05). Conclusion: The study demonstrates a significant relationship between DT, evaluated by both mRSS and US and the percentage of circulating fibrocytes in lcSSc patients. This observation may well support the hypothesis that circulating fibrocytes make a crucial contribution to skin fibrosis progression. References: [1] Cutolo M, et al. Best Pract Res Clin Rheumatol. 2016;30:670-87. 2. Krieg T, et al. Rheumatology 2009;48:iii14-8. 3. Clements PJ, et al. J Rheumatol 1995;22:1281-5. 4. Ruaro B, et al. Arthritis Rheumatol 2015; 67 (suppl 10). 5. Cutolo M, et al. Arthritis Res ther. 2018;20:157. 6. Brunasso aM, et al. F1000Res. 2016 apr 22;5. doi: 10.12688/f1000research.7986.1. 7. Reilkoff R, et al. Nat Rev Immunol. 2011;11:427-35. 8. van den Hoogen F, et al. Ann Rheum Dis. 2013;72:1745-55. Disclosure of interests: None declared